Metabolism-driven and high-efficiency mining of ethanol-tolerant microorganisms from pit mud microbiota using Raman-activated cell sorting - Teng Xu; Qing Sun; Gongchao Jing; Yongming Duan; Xiaohang Wang; Xinyun Yi; Changle Wu; Huizi Zhu; Bo Ma; Jian Xu; Xiaowei Zheng; Xixian Wang; et al. (Bioresource Technology, 2026)

Atomic-scale Cu in situ confined in ZIF-8 as a chemical-biomolecular bridge for visible-light-activated therapy of Staphylococcus aureus biofilm-associated skin infections - Xuehua Chen; Tai-Cheng Zhou; Hao Wang; Xilun Wang; Zhiguo Zhu; Changle Wen; Xiaoxiao Shi; Hanglin Li; Yang Tang; Jia Wei (Chemical Engineering Journal, 2026)

Polystyrene microplastic exposure induces hepatic damage via immune-modulated autophagy and ferroptosis in Nile tilapia (Oreochromis niloticus) - Feilong Wang; Xiaolong Fan; Xiaomeng Guo; Na Guo; Tian Gao; Changle Zhao; Yuanyuan Li; Haiyan Xu; Fan Bai; Yixin Chen; Deshou Wang; Lina Sun; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Diachronous type-shift of banded iron formations responded the form of supercratons - Mengmeng Shen; Jilian Jiang; Changle Wang; Xinyu Zou; Kangkang Gao; Huaqiao Zhang; Peng Peng; Mingguo Zhai (Precambrian Research, 2026)

Assessing the Environmental and Ecological Consequences of Beach Nourishment Projects in Erosion-Prone Areas: A Case Study of Sanya Bay, Hainan, China - Yongzhi Wang; Zichen Zhu; Jun Du; Changle Zhang (Journal of Ocean University of China, 2026)

Effects of six weeks of hypoxia and hypoxic SIT on oxidative stress and myokine responses in skeletal muscle of high-fat–fed ApoE−/− mice - Yangwenjie Wang; Jessica Lavier; Linjia Wang; Weicheng Hua; Hao Wei; Changle Zhao; Maxime Pellegrin; Grégoire P. Millet; Ying Zhang (European Journal of Applied Physiology, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Time-dependent biphasic dysregulation of autophagy and innate immunity underlies polystyrene microplastics-induced hepatotoxicity in Nile tilapia - Feilong Wang; Xiaomeng Guo; Na Guo; Xiaolong Fan; Haiyan Xu; Yuanyuan Li; Tian Gao; Yixin Chen; Changle Zhao; Lina Sun; Deshou Wang; Xin Xie; et al. (Aquatic Toxicology, 2026)

Multiphysics modeling of synergistic microwave heating and nitrogen injection for methane hydrate recovery - Xiaowei Zhang; Yanlong Guan; Changle Yue; Zhigang Sun; Huiying Guo; Yuankai Zhang; Diansheng Wang; Yudou Wang (Fuel, 2026)

Nile tilapia gfra1a mutation leads to failure of endogenous-to-exogenous nutrient source transition with intestinal oxidative stress - Lei Liu; Jiaxin Tan; Changle Zhao; Xi Peng; Yangtian Huang; Deshou Wang; Jing Wei (Aquaculture, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Nondestructive testing of grain moisture content and bulk density by microwave reflection quadrature mixing - Chenxiao Li; Changle Fan; Zuoqi Wang; Xuemeng Sun; Qian Song; Yanlei Xu (Journal of Stored Products Research, 2026)

Statistical knowledge-guided multi-classification machine learning modeling scheme for landslide susceptibility levels - Feifei Zhang; Changle Li; Yuewei Wang; Yiyue Wang (Engineering Geology, 2026)

Hepatic cyp24a1 serves as a biomarker for diagnosing polystyrene microplastic exposure in Nile tilapia (Oreochromis niloticus) - Feilong Wang; Haiyan Xu; Xiaomeng Guo; Xiaolong Fan; Yuanyuan Li; Tiao Gao; Xin Xie; Na Guo; Fan Bai; Yixin Chen; Changle Zhao; Deshou Wang; et al. (Aquatic Toxicology, 2026)

Geological disaster causes analysis based on knowledge graph link prediction - Xinya Lei; Changle Li; Yuewei Wang; Weijing Song (Natural Hazards, 2025)

Functional identification of two Glycerol-3-phosphate Acyltransferase5 homologs from Chenopodium quinoa - Zhen Wang; Yuxin Liu; Haodong Huang; Zhifu Zheng; Shiyou Lü; Xianpeng Yang; Changle Ma (Plant Science, 2025)

Five new chromane meroditerpenoids from the brown alga Sargassum siliquastrum of China Sea - Junzhi Pan; Huayuan Liu; Junpeng Xu; Xiaofeng Xu; Yu Qi; Chaojie Wang; Changle Wu; Zhongmin Sun; Yali Lv; Pengcheng Yan (Phytochemistry Letters, 2024)

Unraveling the Molecular Mechanism of Lignin Accumulation in Stipule Thorns of Zanthoxylum bungeanum: Insights from Transcriptomic and Targeted Metabolomic Analysis - Weilong Gao; Ling Zhou; Hao Zhong; Yuan Meng; Changle Li; Jianxin Wang; Jia Yao; Yulin Liu (Journal of Plant Growth Regulation, 2024)

A combined denoising method for Q-factor compensation of poststack seismic data - Peng Zhang; Qinghan Wang; Yang Liu; Changle Chen (Journal of Applied Geophysics, 2024)

A craton-wide geochemical survey of late Archean banded iron formations in China - Changle Wang; Zhiguo Dong; Leslie Robbins; Banglu Zhang; Zidong Peng; Xiaoxue Tong; Lianchang Zhang; Kurt Konhauser (Earth and Planetary Science Letters, 2024)

W single-atom mediated singlet oxygen formation on carbon nitride for powerful photocatalytic abatement of organic pollutants - Jiaqi Chen; Zhaoxiong Yan; Yingjie Ding; Guosheng Wang; Changle Li; Zhihua Xu (Chemical Engineering Journal, 2024)

The cellular expression patterns of gdnfa and gdnfb in the gonads of Nile tilapia and their differential response to retinoic acid - Lei Liu; Jianeng Li; Changle Zhao; Ximei Qu; Xiang Liu; Deshou Wang; Jing Wei (Theriogenology, 2024)

Oolitic ironstones, continental iron flux and reverse weathering in the Proterozoic Eon: Insights from the Tonian Katherine Group, Yukon - Maxwell Lechte; Galen Halverson; Malcolm Wallace; Timothy Gibson; Ashleigh van Smeerdijk Hood; Changle Wang; Thi Hao Bui; Katie Maloney; Alexie Millikin (Earth-Science Reviews, 2024)

Geochemistry and Sm─Nd─Fe─Si isotope compositions as insights into the deposition of the late Neoarchean Qidashan banded iron formation, North China Craton - Changle Wang; Zidong Peng; Xiaoxue Tong; Liang Gao; Lianchang Zhang (Mineralium Deposita, 2024)

Deciphering the source of banded iron formations in the North China Craton - Changle Wang; Shangjun Xie; Xin Zhang; Xiaoxue Tong; Yang Bai; Zidong Peng; Zhiguo Dong; Lianchang Zhang; Bo Wan (Precambrian Research, 2024)

The organic–inorganic dual anchoring strategy based on organic chelators and lacunary polyoxometalates for the preparation of efficient CoWS hydrodesulfurization catalysts - Wenjing Bao; Cong Zhang; Dengwei Yan; Fengyue Sun; Changle Yue; Chongze Wang; Yukun Lu (Fuel, 2024)

Functional graphitic carbon nitride/hydroxyapatite heterojunction for robust formaldehyde removal at ambient temperature - Zhihua Xu; Changle Li; Nenghuan Wang; Yingjie Ding; Zhaoxiong Yan; Qin Li (Journal of Environmental Chemical Engineering, 2024)

Decoupled neodymium and hafnium isotopes in seawater as insights into the Late Neoarchean weathering process - Zidong Peng; Changle Wang; Lianchang Zhang; Mingguo Zhai (Precambrian Research, 2023)

Mid-Ludfordian uranium isotope records distinguish the role of expansive marine anoxia in global carbon cycle dynamics during the late Silurian Lau/Kozlowskii bioevent - Álvaro del Rey; Jiří Frýda; Mikael Calner; Barbora Frýdová; Feifei Zhang; Changle Wang; Noah Planavsky; Tais W. Dahl (Global and Planetary Change, 2023)

Molecular mechanism of metamorphic alteration on traces of early life in banded iron formations - Jingbo Nan; Zidong Peng; Chao Wang; Dominic Papineau; Zhenbing She; Zixiao Guo; Xiaotong Peng; Junlie Zhou; Yingjie Hu; Weiqi Yao; Ruiling Zhang; Changle Wang; et al. (Earth and Planetary Science Letters, 2023)

Study on the Damping Effect and Mechanism of Vertical Slotted Screens Based on the BM-MPS Method - Changle Zhang; Lizhu Wang; Min Xu (Journal of Marine Science and Engineering, 2023)
Liquid sloshing is a common phenomenon in ocean engineering, and one which not only affects the stability of ship navigation, but also poses a threat to both the marine environment and human life. Ascertaining how best to reduce the amplitude of liquid sloshing has always been a key problem in ocean engineering. In this study, based on an improved moving-particle semi-implicit method, the BM-MPS method, the damping effect of a vertical slotted screen under rotation excitation was simulated and studied, and the influence of baffle porosity and the rotation amplitude on the resonance period and impact pressure was discussed. The results showed that the porosity had an obvious effect on the resonance period. A significant resonance period transformation happened when the porosity was 0.1, but a porosity of 0.15 was the point at which the maximum impact pressure in the resonance was at its minimum. Meanwhile, the impact duration curve was related to porosity. With the increasing of porosity, the impact duration curve changed from having no peak to a single peak, and then to double peak. In addition, the amplitude of rotation excitation was also one of the factors that affected the resonance period.

Seasonal variation in mercury and methylmercury production in vegetated sediment in the Dongtan wetlands of the Yangtze River Estuary, China - Changle Zhu; Shaoyang Lv; Qing Zhao; Xia Liu; Zhigang Wang; Xiangmin Zheng; Limin Zhou; Yongjie Wang (Marine Environmental Research, 2023)

Microwave-driven upcycling of single-use plastics using zeolite catalyst - Yuxin Wang; Tara Biddle; Changle Jiang; Thang Luong; Roujia Chen; Siobhan Brown; Xiangyu Jie; Jianli Hu (Chemical Engineering Journal, 2023)

Regulatory role of myo-inositol in the ovarian development of female Chinese mitten crab (Eriocheir sinensis) - Xianyong Bu; Qincheng Huang; Ying Song; Changle Qi; Zhideng Lin; Xiaodan Wang; Meiling Zhang; Chuanjie Qin; Jian G. Qin; Liqiao Chen (Aquaculture, 2023)

Thermodegradation of naturally decomposed forest logging residues: Characteristics, kinetics, and thermodynamics - Wanhe Hu; Jingxin Wang; Jianli Hu; Jamie Schuler; Shawn Grushecky; Nan Nan; William Smith; Changle Jiang (Bioresource Technology, 2023)

Archean to early Paleoproterozoic iron formations document a transition in iron oxidation mechanisms - Changle Wang; Leslie J. Robbins; Noah J. Planavsky; Nicolas J. Beukes; Laureline A. Patry; Stefan V. Lalonde; Maxwell A. Lechte; Dan Asael; Christopher T. Reinhard; Lianchang Zhang; Kurt O. Konhauser (Geochimica et Cosmochimica Acta, 2023)

Superhydrophilic molybdenum phosphide quantum dots on porous carbon matrix for boosting hydrogen evolution reaction - Yang Liu; Changle Yue; Fengyue Sun; Wenjing Bao; Lulu Chen; Zonish Zeb; Chongze Wang; Shuyan Ma; Cong Zhang; Daofeng Sun; Yuan Pan; Yichao Huang; et al. (Chemical Engineering Journal, 2023)

BSA‑seq and genetic mapping identified candidate genes for branching habit in peanut - Jiaowen Pan; Ximeng Zhou; Naveed Ahmad; Kun Zhang; Ronghua Tang; Huiling Zhao; Jing Jiang; Mengdi Tian; Changsheng Li; Aiqin Li; Xianying Zhang; Liangqiong He; et al. (Theoretical and Applied Genetics, 2022)

Insight into the genesis of the Zhaosu Carboniferous Mn carbonate deposit (NW China): constraints from petrography, geochemistry, and C–Mo isotopes - ZhiGuo Dong; ZiDong Peng; ChangLe Wang; BangLu Zhang; LianChang Zhang; Jie Li; Xin Zhang; WenJun Li; Le Zhang (Mineralium Deposita, 2022)

BSA‑seq and genetic mapping reveals AhRt2 as a candidate gene responsible for red testa of peanut - Kun Zhang; Mei Yuan; Han Xia; Liangqiong He; Jing Ma; Mingxiao Wang; Huiling Zhao; Lei Hou; Shuzhen Zhao; Pengcheng Li; Ruizheng Tian; Jiaowen Pan; et al. (Theoretical and Applied Genetics, 2022)

Legionella feeleii: pneumonia or Pontiac fever? Bacterial virulence traits and host immune response - Changle Wang; Xia Chuai; Mei Liang (Medical Microbiology and Immunology, 2019)

Purinergic P2X7 receptor functional genetic polymorphisms are associated with the susceptibility to osteoporosis in Chinese postmenopausal women - Hong Xu; Chengxin Gong; Luling He; Shenqiang Rao; Xingzi Liu; Yijun Nie; Changle Liu; Tao Li; Lu Ding; Yunming Tu; Yuping Yang; Fangfang Hu; et al. (Purinergic Signalling, 2017)

Depositional environment and origin of the Lilaozhuang Neoarchean BIF-hosted iron–magnesite deposit on the southern margin of the North China Craton - Hua Huang; LianChang Zhang; Sébastien Fabre; ChangLe Wang; MingGuo Zhai (International Journal of Earth Sciences, 2017)

Rare earth element and yttrium compositions of the Paleoproterozoic Yuanjiacun BIF in the Lüliang area and their implications for the Great Oxidation Event (GOE) - ChangLe Wang; LianChang Zhang; CaiYun Lan; YanPei Dai (Science China Earth Sciences, 2014)

Transcriptomic profiling revealed an important role of cell wall remodeling and ethylene signaling pathway during salt acclimation in Arabidopsis - Xiaoyan Shen; Zenglan Wang; Xiaofeng Song; Jiajia Xu; Chunyun Jiang; Yanxiu Zhao; Changle Ma; Hui Zhang (Plant Molecular Biology, 2014)

Association of CDKN1B gene polymorphisms with susceptibility to breast cancer: a meta-analysis - Heping Xiang; He Li; Weiwei Ge; Weidong Wu; Ming Gao; Wei Wang; Lei Hong; Datong Jiang; Changle Zhang (Molecular Biology Reports, 2013)